Synthesis of benzylated amine-substituted xanthone derivatives and their antioxidant and anti-inflammatory activities - Wong, Ka Woong; Teh, Soek Sin; Law, Kung Pui; Ismail, Intan Safinar; Sato, Kohei; Mase, Nobuyuki; Mah, Siau Hui (Wiley, 2022)
Oxidative stress and its constant companion, inflammation, play a critical part in the pathogenesis of many acute and chronic illnesses. The discovery of new multi-targeted drug candidates with antioxidant and anti-inflammatory properties is deemed necessary. Thus, a series of novel xanthone derivatives with halogenated benzyl (4b-4d, 4f-4h) and methoxylated benzyl groups (4e) attached to the butoxy amine substituent were synthesized in this study. The synthesized xanthone derivatives exhibited stronger antioxidant activity against H2 O2 scavenging than the standard drug, α-tocopherol, but weaker towards DPPH scavenging and ferrous ion chelation. Besides that, 4b-4d, 4f-4h demonstrated good anti-inflammatory activities through NO production inhibition towards lipopolysaccharide (LPS)-induced RAW 264.7 cells and showed 2-4 times stronger effects than the standard drug, diclofenac sodium. Moreover, compound 4b with two brominated benzyl groups attached to the butoxy amine substituent suppressed the production of pro-inflammatory cytokines, TNF-α and IL-1β, significantly. Structure-activity relationship elucidated that the halogenated benzylamine substituent plays an important role in contributing the antioxidant and anti-inflammatory activities of xanthones. In summary, xanthone 4b was identified as a potential lead compound to be further developed into antioxidant and anti-inflammatory drugs. Thus, further studies on the related mechanisms of action of 4b are recommended.